Assessment of Instructional Strategies Employed by Physics Teachers and Students Academic Achievement in Secondary Schools in Rivers State - Doris, Omeodu, M. (European Scientific Journal, ESJ, 2019)
The study assessed instructional strategies employed by Physics teachers and students academic achievement in Secondary schools in Rivers State. The study in specific terms, assessed the instructional strategies employed by physics teachers, determine the level of use of instructional strategies in the teaching of Physics and determine the difference in the academic achievement of those taught with frequently used instructional strategies in Rivers State. The population of the study consisted of all practicing Physics teachers and students in Rivers State. The sample size of the study was 28 Physics teaachers selected from 18 science teaching schools in Rivers State and 140 science students from 4 schools whose teachers indicated usage of any of the frequently used instructional strategies. A structured questionnaire and Physic Achievement Test (PAT) was used to collect data from Physics teachers and students respectively. Frequency, Mean and standard deviation was used to analyze the gathered data, while z-test was used to test hypotheses at 0.05 level of significance. In the study, among the traditional instructional strategies, it was found that lecture method, demonstration method, laboratory method and problem solving method of teaching are the most frequently used strategies employed by Physics teachers in Rivers State. However, when the students who were taught Physic by these most frequently used strategies were tested, it was found that students who were frequently taught Physics with demonstration method achieved more that those taught with lecture method. Similarly, students taught with problem solving methods achieved more than those who were frequently taught with laboratory strategy. It was recommended that Physics teachers should employ instructional strategies that will actively engage students in the lesson.